OPTIMALISASI PENGKADERAN AL-ISLAM DAN KEMUHAMMADIYAHAN BAGI CALON KEPALA SEKOLAH MUHAMMADIYAH DI PONOROGO - Wahyudi Wahyudi; Sumaji Sumaji; Intan Sari Rufiana (Jurnal Abdimas Bina Bangsa, 2022)
An organization must have an understanding that is truly agreed upon by all members. One of the spread Islamic organizations in Indonesia is Muhammadiyah. This organization is very influential and contributes in upholding and fighting for integrity in Indonesia. In this case, the branch level Muhammadiyah organization, especially in Ponorogo, in education there is a regeneration of Muhammadiyah school principals. In this case, to become the head of a Muhammadiyah school in Ponorogo, the prospective headmaster of Muhammadiyah must have the same understanding in this organization, namely Muhammadiyah. In addition, prospective headmasters of Muhammadiyah schools must understand and understand the true ideas and thoughts of Muhammadiyah. So that later, the prospective headmaster of Muhammadiyah in carrying out this mandate, can continue and maintain the values of Al-Islam and Kemuhammadiyahan which are embedded in the Muhammadiyah organization. This matter was conveyed by the dikdasmen assembly to one of the cadres at universities, namely Muhammadiyah University of Ponorogo to conduct a briefing and cadre for prospective Muhammadiyah school principals in Ponorogo. Thus, this rehearsal activity was formed and will be carried out with the aim of conducting cadre for prospective Muhammadiyah school principals in Ponorogo. This is done to provide provision for them, so that they have the same understanding, intention and determination when later in carrying out this mandate they can implement the values of Al-Islam and Muhammadiyah correctly